Leading ventricular cardiomyocytes - Rosero Salazar, Doris Haydee; Ortiz Salazar, Mario Alejandro; Salazar Monsalve, Liliana (Universidad y Salud, 2015)
Objective: To expose the histological and functional characteristics that occur in heart striated muscle tissue specialized in the conduction of electrical stimulation and its current implications for cardiac arrhythmias. Materials and methods: Publications in indexed journals in PubMed, Wiley, Ovid-Medline and Science Direct databases were selected. The MESH descriptors used for the search were cardiac myocytes, myocardium and heart conduction system. The concepts of histology and arrhythmia were mated. Articles published from 1990 to 2014 were reviewed as well as the original ones, case reports and reviews related to the concepts of embryonic development, cell differentiation and normal morphology alteration of the leading ventricular cardiomyocytes. The summary of 317 articles were read, from which 75 were classified to complete reading and finally 52 were selected for the drafting of this article. Conclusion: Current studies are directed towards the driving system simulation to establish other causes of arrhythmia and its treatment options. Not only therapies with undifferentiated cells and molecular genetic modification techniques are part of these studies but also the implementation of alternative therapies that are not invasive in the treatment of cardiac arrhythmias.